Interdisciplinary Curriculum and Simulation Cases for Teaching Leadership and Communication to Medical Rapid Response Teams - Lisa Motz; Benjamin Lloyd; Anthony Donato; Ashok Chaudhary; Antony Kaliyadan; Debra Haas Stavarsk; Carol M. Diehl; Deanna Reber; Barbara Romig; Eileen Ravert (Association of American Medical Colleges, 2012)
Abstract This guide contains materials to teach internal medicine residents and rapid response team members the leadership and communication skills to run a rapid response team in management of acute medical problems. The enclosed instructor guide and the attached materials are designed to train an interdisciplinary team consisting of a floor nurse, an ICU nurse, a respiratory technician, and an internal medicine senior resident; in other words the core of a team who may be responsible for rapid response in the hospital wards. The training is designed to teach teams at regular, short intervals by applying intensive training with brief feedback cycles that are intended to be as unobtrusive to schedules as possible with the goal of assembling all members of a team to teach communication and leadership principles. This format is undertaken to accomodate those with ongoing clinical responsibilities. The course curriculum describes the learning objectives for each team member and the program structure. The simulation scenarios were developed for use with Laerdal SimMan 3G, although the materials provided could potentially be adapted to other systems. Using a posttest survey, resident ratings of their pretest comfort with leading a Rapid Response Team was measured at 2.86 (1-6 scale; 1 = no experience, 6 = expert level), and their ratings at the end were measured at 4.53, which was significant by paired t-test analysis (p < .001). Residents described this as a "valuable experience" on a Likert scale with an average of 4.53 (standard Likert, 1 = strongly disagree, 5 = strongly agree).